Impact of sowing date and level of phosphorus application on economic returns in cotton - Tlatlaa, Jacob Shauri; Tryphone, George Muhamba; Nassary, Eliakira Kisetu (Frontiers in Plant Science, 2024)
This study explored the economic dynamics of cotton (Gossypium hirsutum L.) production in Msilale village, Chato District, Tanzania. The experiment utilized a factorial design with sowing dates on November 25 th , December 15 th , and January 4 th , and phosphorus levels at 0, 20, 40, and 60 kg P ha -1 , replicated three times.Results indicated significantly higher cotton yields (6.1 t ha -1 and 6.3 t ha -1 ) for November and December sowings compared to January (3.8 t ha -1 ). This is a 61% and 66% increase in cotton yields for November and December sowings, respectively relative to January sowing. Though not significant, 20 kg P ha -1 and 40 kg P ha -1 applications yielded 5.8 t ha -1 and 5.4 t ha -1 , respectively, while 60 kg P ha - 1 yielded 5.3 t ha -1 . This is a 9.4% and 1.9% increase in cotton yields at 20 and 40 kg P ha -1 , respectively relative to absolute control and 60 kg P ha -1 application.Economic analysis revealed that late sowing (January) had the lowest net profit (Tshs. 3,723,400 ≈ USD 1,486) and benefit-to-cost ratio (BCR) of 11.2. Early sowings recorded higher net profits (Tshs. 6,679,527 ≈ USD 2,666 and Tshs. 6,861,283 ≈ USD 2,738) and BCRs (18.4 and 18.8, respectively). This is a 79% (BCR = 64%) and 84% (BCR = 68) increase in net benefits from early sowings compared to late sowing. Applications of 20, 40, and 60 kg P ha -1 resulted in net benefits of Tshs. 5,452,572 ≈ USD 2,176 (BCR = 19.2), Tshs. 5,209,904 ≈ USD 2,079 (BCR = 15.1), and Tshs. 5,748,786 ≈ USD 2,294 (BCR = 14.1), respectively, with a significant (p = 0.017) BCR at 20 kg P ha -1 indicating cost-effectiveness. This is a 36% and 7.1% economic benefit at 20 and 40 kg P ha -1 , respectively compared to 60 kg P ha -1 application. Optimizing sowing dates and P levels can boost economic returns in cotton production and promote sustainability.